A Pilot Randomized Controlled Trial of Early versus Routine Caffeine in Extremely Premature Infants - Katheria, Anup C.; Sauberan, Jason B.; Akotia, Devang; Rich, Wade; Durham, Jayson; Finer, Neil N. (American Journal of Perinatology, 2015)
Objective This study aims to compare the effects of early and late (routine) initiation of caffeine in nonintubated preterm neonates.Study Design A total of 21 neonates < 29 weeks gestational age were randomized to receive intravenous caffeine citrate (20 mg/kg) or placebo either before 2 hours of age (early) or at 12 hours of age (routine). This was an observational trial to determine the power needed to reduce the need for endotracheal intubation by 12 hours of age. Other outcomes included comparisons of cerebral oxygenation, systemic and pulmonary blood flow, hemodynamics, hypotension treatment, oxygen requirement, and head ultrasound findings.Results There was no difference in the need for intubation (p = 0.08), or vasopressors (p = 0.21) by 12 hours of age. Early caffeine was associated with improved blood pressure (p = 0.03) and systemic blood flow (superior vena cava flow, p = 0.04 and right ventricular output, p = 0.03). Heart rate, left ventricular output, and stroke volume were not significantly affected. Cerebral oxygenation transiently decreased 1 hour after caffeine administration. There were no differences in other outcomes.Conclusion This pilot study demonstrated the feasibility of conducting such a trial in extremely preterm neonates. We found that early caffeine administration was associated with improved hemodynamics. Larger studies are needed to determine whether early caffeine reduces intubation, intraventricular hemorrhage, and related long-term outcomes.
Keywords: caffeine; hemodynamics; intubation; vasopressors